2022
DOI: 10.1186/s13578-022-00757-y
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs and microRNAs as crucial regulators in cardio-oncology

Abstract: Cancer is one of the leading causes of morbidity and mortality worldwide. Significant improvements in the modern era of anticancer therapeutic strategies have increased the survival rate of cancer patients. Unfortunately, cancer survivors have an increased risk of cardiovascular diseases, which is believed to result from anticancer therapies. The emergence of cardiovascular diseases among cancer survivors has served as the basis for establishing a novel field termed cardio-oncology. Cardio-oncology primarily f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 357 publications
(361 reference statements)
0
13
0
Order By: Relevance
“…Third, by guiding the relevant RNA-binding proteins, lncRNAs are able to mediate the target genes via cis- or trans-regulation to specific protein complex sites [ 33 , 34 ]. Fourth, scaffolds, lncRNAs can be used as a platform; on this platform, a variety of related molecular complexes can be combined together to enhance the information transmission and interaction between molecular complexes [ 35 , 36 ]. Studies have found that the growth and development of the body, the occurrence and development of tumors, cell proliferation, and apoptosis are all related to the abnormal expression of lncRNAs, especially in tumorigenesis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, by guiding the relevant RNA-binding proteins, lncRNAs are able to mediate the target genes via cis- or trans-regulation to specific protein complex sites [ 33 , 34 ]. Fourth, scaffolds, lncRNAs can be used as a platform; on this platform, a variety of related molecular complexes can be combined together to enhance the information transmission and interaction between molecular complexes [ 35 , 36 ]. Studies have found that the growth and development of the body, the occurrence and development of tumors, cell proliferation, and apoptosis are all related to the abnormal expression of lncRNAs, especially in tumorigenesis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicates the regulatory role of miRNAs in multiple diseases, 16 however, crucial miRNAs that are known to be involved in the progression of diseases comprise only the tip of the iceberg. The present study investigated the expression pattern of miR-28-5p in CP and its potential mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on cardiac mesenchymal stem cells (cSMC) stimulated with the macrophage migration inhibitory factor (MIF) prior to DOX administration resulted in the formation of MIF-containing exosomes (Exo-MIF) in which lncRNA–NEAT1, suggested to exert a significant role in the cardioprotective process, accumulated [ 51 ]. The results demonstrated that Exo-MIF relieved Dox-induced cardiomyocyte senescence, and these cardioprotective properties were explained by lncRNA NEAT1 presence that regulates these pathways sponging miR-221-3p and had been already found to have protective roles against cell death, apoptosis, and cell senescence [ 57 ]. In particular, miR-221-3p upregulation, through the regulation of SIRT2, could lead the cells in the G0/G1 phase, increase the expression of p27 and p16, while, on the other side, inhibiting telomerase activity, leading the cell to senescence.…”
Section: Studies Conducted On Exosomes In Experimental Modelsmentioning
confidence: 99%